The Effect of Social Media X Usage on the Academic Behavior of FISIP Students at Swadaya Gunung Jati University - Dimas Aditya Senoputra; Herlinda Rahayu; Farida Nurfalah (Syntax Corporation Indonesia, 2025)
In today's digital age, social media X has become an integral part of students' lives and has the potential to influence their academic behavior. This study aims to determine whether there is a significant influence between the use of social media X and the academic behavior of students at the Faculty of Social and Political Sciences, Swadaya Gunung Jati University, as well as to examine whether social media X can encourage academic achievement. This study uses an associative quantitative approach with a survey design through questionnaires, as well as stratified sampling techniques in sampling. Data analysis was performed using simple linear regression using SPSS software. The results of the study show a regression coefficient value of 0.379 (p < 0.001) and an R Square of 0.676. This means that 67.6% of the variation in student academic behavior can be explained by the use of social media X. In other words, this study shows a statistically significant influence between the use of social media X and the academic behavior of FISIP students at Swadaya Gunung Jati University